1998
DOI: 10.1126/science.281.5374.251
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Use of Fire at Zhoukoudian, China

Abstract: Zhoukoudian is widely regarded as having the oldest reliable evidence for the controlled use of fire by humans. A reexamination of the evidence in Layer 10, the earliest archaeological horizon in the site, shows that burned and unburned bones are present in the same layer with stone tools. However, no ash or charcoal remnants could be detected. Hence, although indirect evidence for burning is present, there is no direct evidence for in situ burning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(74 citation statements)
references
References 18 publications
0
71
0
2
Order By: Relevance
“…The revised dating of Pleistocene glacial cycles (e.g., Shackleton et al, 1990;Bassinot et al, 1994) and the stratigraphy of Zhoukoudian (Grü n et al, 1997) make the argument for H. erectus habitation of northern China during glacial periods questionable (Antón, 2002a). Likewise, the argument that H. erectus was probably using and controlling fire (e.g., Black, 1931;Wu, 1999; a claim questioned by recent microstratigraphic work by Weiner et al, 1998Weiner et al, , 1999Goldberg et al, 2001), as well as using clothing, shelter, and perhaps stored food remains (e.g., Turner, 1992) in order to survive the cold climate, is unnecessary (Huang, 1997).…”
Section: Asiamentioning
confidence: 79%
“…The revised dating of Pleistocene glacial cycles (e.g., Shackleton et al, 1990;Bassinot et al, 1994) and the stratigraphy of Zhoukoudian (Grü n et al, 1997) make the argument for H. erectus habitation of northern China during glacial periods questionable (Antón, 2002a). Likewise, the argument that H. erectus was probably using and controlling fire (e.g., Black, 1931;Wu, 1999; a claim questioned by recent microstratigraphic work by Weiner et al, 1998Weiner et al, , 1999Goldberg et al, 2001), as well as using clothing, shelter, and perhaps stored food remains (e.g., Turner, 1992) in order to survive the cold climate, is unnecessary (Huang, 1997).…”
Section: Asiamentioning
confidence: 79%
“…There are a few claims for earlier use of fire in Asia, however, with the case of Zhoukoudian Locality 1 being the most contested one. Although this site was considered for a long time to be the fire-lit home of Homo erectus, studies by Weiner and colleagues (56,57) showed that the "ashes" supposedly reflecting former hearths were not ashes at all: samples from Layers 10 through 3 showed extensive water deposition of fine silt-sized material (reworked loess), including fine-grained organic matter. The dark, organic-rich unit in Layer 10, often cited as some of the earliest evidence of fire, is in fact a water-laid accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Although cooking is clearly an important innovation in hominid evolution that served to increase dietary digestibility and quality, there is very limited evidence for the controlled use of fire by hominids prior to 1.5 Ma (Brain and Sillen, 1988;Bellomo, 1994;Pesini, 1999). The more widely held view is that the use of fire and cooking did not occur until considerably later in human evolution, probably closer to 200-250,000 years ago (Straus, 1989;Weiner et al, 1998), although possibly as early as 400,000 years ago (Preece et al, 2006). In addition, nutritional analyses of wild tubers used by modern foragers (e.g., Schoeninger et al, 2001) suggest that the energy content of these resources is markedly lower than that of animal foods, even after cooking (Cordain et al, 2001).…”
Section: Diet Qualitymentioning
confidence: 99%